Determinan Penerimaan Imunisasi HPV Pada Siswi Sekolah Dasar di Kota Pangkalpinang Tahun 2026 - Aspin Aspin; Ferly Oktriyedi; Heru Listiyono; Taufik Kurrohman; Dedek Sutinbuk (Universitas Pahlawan Tuanku Tambusai, 2026)
Human Papilloma Virus (HPV) is the main cause of cervical cancer and several other types of cancer. Prevention through HPV immunization early is important to reduce the risk of disease due to HPV infection. Analyzing the determinants of HPV immunization acceptance in elementary school students in Pangkalpinang City. This study uses an analytical observational design with a cross-sectional approach. The sample amounted to 338 respondents who were selected using the quota sampling technique. Data were collected through questionnaires and analyzed univariately, bivariately using chi-square test (α=0.05), and multivariate using logistic regression. Bivariate analysis showed a significant relationship between HPV immunization acceptance and knowledge (p=0.000; OR=2.978), social media (p=0.000; OR=3.458), family support (p=0.000; OR=8.969), perception of vulnerability (p=0.000; OR=4.634), perception of seriousness (p=0.000; OR=3.513), perceived benefit (p=0.000; OR=7.575), and perception of resistance (p=0.000; OR=0.347). Multivariate analysis showed that family support was the most dominant factor in HPV immunization acceptance (POR=4.033; p<0.05). Family support plays an important role in increasing HPV immunization acceptance among elementary school students, so it needs to be strengthened through health education and immunization promotion.